Sosialisasi UMKM Desa Sukamurni melalui Portal Wisata Industri Sarana Promosi Ekonomi dan Pariwisata Kabupaten Bekasi - Abdulloh Kafabbih; Fajar Prihesnanto; Setyo Supratno; Rika Sylviana (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
The advancement of digital technology plays a crucial role in fostering regional economic growth and tourism. Bekasi Regency, recognized as Indonesia’s largest industrial area, has vast potential to develop its tourism sector and creative economy. However, limited public understanding of digital utilization remains a major challenge, particularly in promoting village potential and local products in Sukamurni. To address this issue, and the socialization of the Industrial Tourism Portal was carried out to improve community skills and awareness of technology as an effective promotional tool. The program adopted a participatory approach through counseling, training, and direct practice, enabling active engagement of participants throughout the process. The residents of Sukamurni Village became the main actors in using the portal to highlight local tourism and broaden the market reach of MSME products. The outcomes indicated that participants not only gained theoretical knowledge but also practical competence in accessing and applying portal features effectively. Moreover, the activity successfully raised awareness of the significance of digitalization in enhancing business competitiveness and long-term sustainability. With this important initiative, and Sukamurni Village is expected to strengthen its position as an innovative, productive, and technology-adaptive tourism village, while also actively supporting sustainable community welfare and inclusive regional development.